Business Management and Feasibility Of Beef Cattle In Muaro Jambi District - Sophia Sophia; Asaibani Asaibani; Endang Meiliani; Afriantoni Afriantoni (Fakultas Pertanian Universitas Muara Bungo, 2023)
This study aims to analyze the management and feasibility value of beef cattle business in Muaro Jambi Regency. The focus of this research area was carried out in Bahar Mulya Village, Bahar Utara District, Muaro Jambi Regency, this area was chosen as the research location with the consideration that most of the people in this area have side businesses as beef cattle breeders. The number of samples is 30 people. This study uses two kinds of data collection methods, namely primary data and secondary data. Primary data collection techniques include surveys and structured interviews. During the interview, questions were asked to respondents based on a questionnaire that had been prepared to explore the data that they wanted to know in the research. The results showed that the management of the beef cattle business in the study area was still managed traditionally by applying the cattle umbaran system. Financially, the potting cattle business was declared feasible with an NPV feasibility value of 345,606,133 and a Net B/C value of 2. 10.